Tecnologia e sustentabilidade: a utilização da ferramenta Google Classroom aplicada ao processo ensino e aprendizagem - SILVA, Thayna Vanessa Alves da (Brasil, 2021)
Awareness about sustainable practices in the educational environment must be worked on in the school routine. In the classroom, in addition to being in the students' learning, it must promote socio-environmental attitudes, since for most school activities, paper is the most used item. The introduction of educational technologies, in addition to promoting innovative, dynamic and interactive classes, can collaborate with the fight against the excessive use of paper in the school environment, favoring the environment. It is perceived that technology in education as a sustainable tool, can lead to considerable paper savings, reducing the negative effect in the face of the many trees that are felled for the extraction of cellulose. Thus, educational technologies can become great allies in the construction of sustainable practices in the school environment, as any discipline, material or content can have activities and assessments prepared, built and carried out with technological resources. In view of the above, this research work was based on a qualitative research-action, developed with a professor in a group of Médiotec of the Technical Course of Medium Level in Maintenance and Support in Computer Science. The objective was to promote innovative and sustainable pedagogical strategies based on the Google Classroom virtual platform use in the students' teaching / learning process, and, at the same time, to point out technological solutions to contain excessive paper expenditure in classroom class. The results showed that there was more interaction, dynamism in the classes, added to the understanding and sensitivity of the subjects involved regarding socioenvironmental responsibility in the educational environment.